2019
DOI: 10.1371/journal.pone.0216748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with lysozyme on the structure and function of the cecal microbiota in broiler chickens

Abstract: Lysozyme is known to eliminate intestinal pathogens in poultry and improve their growth performance. However, whether it can replace antibiotic growth promoters without the associated risk of the emergence of antibiotic-resistant bacterial strains is not known, and the effects of lysozyme supplementation on the composition, biodiversity, and function of the chicken gut microbiota remain unclear. Here, we used the 16S rRNA gene and ITS fragment Illumina sequencing combined with transcriptomic analysis to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“…The possible explanation to the inconsistencies might be the constructional and functional differences of the GIT between birds and mammals, as well as the sensitivities of the microbiome to FA in the diverse animal species. Previous papers illustrated that cecal bacterial microbiome of birds were usually dominated by members of the phyla Bacteroidetes and Firmicutes , followed by lower abundance of Proteobacteria , Actinobacteria and others ( Costa et al, 2017 ; She et al, 2018 ; Xia et al, 2019 ). It was consistence with the cecal microbial construction in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation to the inconsistencies might be the constructional and functional differences of the GIT between birds and mammals, as well as the sensitivities of the microbiome to FA in the diverse animal species. Previous papers illustrated that cecal bacterial microbiome of birds were usually dominated by members of the phyla Bacteroidetes and Firmicutes , followed by lower abundance of Proteobacteria , Actinobacteria and others ( Costa et al, 2017 ; She et al, 2018 ; Xia et al, 2019 ). It was consistence with the cecal microbial construction in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Genera mentioned were significantly higher than compared to their two adjacent sections. Significance was assigned if adjusted p-values < 0.01. involved in the degradation of non-starch polysaccharides and monosaccharides [62,63]; a function that could translate to shorebird caeca.…”
Section: Microbial Function In the Shorebird Microbiomementioning
confidence: 99%
“…The higher diversity of intestinal bacteria might be beneficial for the Hooded Cranes at Shengjin Lake to obtain nutrients effectively from indigestible and nutrient-limited food [ 53 ]. Indeed, our study showed that the Hooded Cranes at Shengjin Lake harbored more abundant genus, such as Bacillus, Clostridium and Paenibacillus which can metabolize cellulose and improve the degradation of non-starch polysaccharides ( Figure 5 ) [ 54 , 55 ]. In addition, we found that the genera Anaerorhabdus and Ewingella were more abundant in the gut of the Hooded Cranes at Caizi Lake, which might be detrimental for the host and increase the risk of host infection, respectively ( Figure 5 ) [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%